La aplicación del marketing relacional en mercados masivos de América Latina: estudio de casos en el Perú - Wakabayashi, José (2013)
Relational marketing appeared as an attempt to overcome the constraints of transactional marketing, aiming to develop and preserve long term relations with clients by satisfying their needs and increasing value. In practice, however, there is no accurate understanding of the way the Relational Marketing has been applied in Latin American mass consumer markets and in particular, Peru. In response, a multiple case study was conducted, compiling and analyzing data from three companies in Lima, Peru, to determine the applications of these marketing paradigms. The most significant findings reveal that in applicative fields the transactional and relational paradigms are applied simultaneously, thus denying any potential evolution from the former to the latter.